2009
DOI: 10.1673/031.009.0701
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Descending Visually-Sensitive Neurons in the Hawkmoth,Manduca sexta, to Three-Dimensional Flower-Like Stimuli.

Abstract: Hawkmoths rely on vision to track moving flowers during hovering-feeding bouts. Visually guided flight behaviors require a sensorimotor transformation, where motion information processed by the optic ganglia ultimately modifies motor axon activity. While a great deal is known about motion processing in the optic lobes of insects, there has been far less exploration into the visual information available to flight motor axons. Visual information recorded at this stage has likely arisen from multiple visual pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Except for broadbilled hummingbirds, all the birds had reaction times much lower than those reported for the visual feedback of insects. For example, hawkmoths have >50 ms delays in responding to moving flowers (Sprayberry, 2009), and fruit flies have ∼100 ms and ∼61 ms delays in responding to gust perturbation and looming-startling stimuli, respectively (Fuller et al, 2014;Muijres et al, 2014). These data reveal that hummingbirds are capable of faster visual processing than insects.…”
Section: Escape Reaction Timementioning
confidence: 96%
“…Except for broadbilled hummingbirds, all the birds had reaction times much lower than those reported for the visual feedback of insects. For example, hawkmoths have >50 ms delays in responding to moving flowers (Sprayberry, 2009), and fruit flies have ∼100 ms and ∼61 ms delays in responding to gust perturbation and looming-startling stimuli, respectively (Fuller et al, 2014;Muijres et al, 2014). These data reveal that hummingbirds are capable of faster visual processing than insects.…”
Section: Escape Reaction Timementioning
confidence: 96%
“…We used values of   ranging from 0 to 2 wingbeats and  ranging from 0 to 0.5 wingbeats, assuming low latencies in the mechanosensor-based angular velocity sensing (Sane et al, 2007) and the larger latencies of typical of visual sensing (Sprayberry, 2009) for pitch angle detection. Similar to the no-delay case, K x , K a and K  can be obtained from fits to measured x(t) and b (t) with  b and b offset by the specified delays.…”
Section: Deng and T L Hedrickmentioning
confidence: 99%
“…Sun and Xiong, 2005) and that angular velocity sensors likely operate with lower latency than visual angular position sensing (e.g. Sane et al, 2007;Sprayberry, 2009). Our stability analysis also revealed that, given sufficient derivative feedback, the moth could stabilize its pitch without use of proportional feedback, but that incorporating both modes substantially increased stability.…”
Section: Closed-loop Control Inputs and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…They modify the activity of thoracic networks to adapt specific behaviors depending on current stimulus conditions. Previous studies on descending visual neurons have analyzed looming-sensitive neurons mediating escape (Rind et al, 2008;Fotowat et al, 2009;Yamawaki and Toh, 2009), deviation detector neurons controlling flight balance (Griss and Rowell, 1986;Rowell and Reichert, 1986;Hensler, 1988Hensler, , 1992Hensler and Rowell, 1990), neurons coding for self-motion (Wertz et al, 2008(Wertz et al, , 2009a, targetselective neurons mediating prey detection (Olberg, 1986;Frye and Olberg, 1995), and figure-detecting neurons involved in flower recognition (Sprayberry, 2009). Descending neurons mediating sky compass-related polarization information should encode two important factors: the position of the sun and the daytime.…”
Section: Introductionmentioning
confidence: 99%